2019
DOI: 10.3389/fped.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Bronchopulmonary Dysplasia: Evidences From Microbiomics, Metabolomics, and Proteomics

Abstract: Bronchopulmonary dysplasia is a major issue affecting morbidity and mortality of surviving premature babies. Preterm newborns are particularly susceptible to oxidative stress and infants with bronchopulmonary dysplasia have a typical oxidation pattern in the early stages of this disease, suggesting the important role of oxidative stress in its pathogenesis. Bronchopulmonary dysplasia is a complex disease where knowledge advances as new investigative tools become available. The explosion of the “omics” discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 87 publications
(83 reference statements)
0
24
0
Order By: Relevance
“…Overall, these findings suggest that quality improvement of perinatal and neonatal intensive care as evidenced by improved survival of peri-viable infants at 23-24 weeks' gestation could not only improve survival but also reduce morbidity rates of extremely preterm infants 7,28,30,31,33 . Given that oxygen toxicity increases the risk of death, BPD and ROP in the premature infants [3][4][5][6]29,34,35 , the controversial association of decreased ROP, BPD and survival observed in the lower oxygen saturation setting of 85-89%, and the increased ROP, BPD and survival observed in the higher oxygen saturation setting of 91-95% [12][13][14][15][16][17][18][19][20][21][22][23][24] is difficult to explain. For international comparison of neonatal research networks, the Japanese neonatal research network with the highest survival rate and proportion of infants at 24 weeks' gestation reported the highest BPD and ROP treatment rates, whereas the Swiss neonatal network with a low survival and proportion of infants at 24 weeks' gestation reported the lowest BPD and ROP treatment rates 2,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings suggest that quality improvement of perinatal and neonatal intensive care as evidenced by improved survival of peri-viable infants at 23-24 weeks' gestation could not only improve survival but also reduce morbidity rates of extremely preterm infants 7,28,30,31,33 . Given that oxygen toxicity increases the risk of death, BPD and ROP in the premature infants [3][4][5][6]29,34,35 , the controversial association of decreased ROP, BPD and survival observed in the lower oxygen saturation setting of 85-89%, and the increased ROP, BPD and survival observed in the higher oxygen saturation setting of 91-95% [12][13][14][15][16][17][18][19][20][21][22][23][24] is difficult to explain. For international comparison of neonatal research networks, the Japanese neonatal research network with the highest survival rate and proportion of infants at 24 weeks' gestation reported the highest BPD and ROP treatment rates, whereas the Swiss neonatal network with a low survival and proportion of infants at 24 weeks' gestation reported the lowest BPD and ROP treatment rates 2,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BPD in preterm infants with a gestational age of 30 weeks is 12%; the incidence with a gestational age of 25 to 26 weeks is 30-40% [8].In this study, the gestational age and birth weight of the BPD group were low, and multivariate analysis showed that birth gestational age < 30 weeks and birth weight < 1000 g were risk factors for BPD. This was consistent to the previous research results.…”
Section: Multivariate Logistic Regression Of Bpd Influencing Factorsmentioning
confidence: 49%
“…Among the most promising drugs, according to our study, are those for the prevention of neurological damage, such as melatonin, retinoid lactoferrin, and vitamin E ( Figure 2). The microbiome has an important role in oxidative stress; in fact, the use of lactobacilli might be protective against OS lesions in preterm infants [97]. The search for new biomarkers, the improvement of care within the NICU, and the use of new machines and increasingly precise techniques for the study of oxidative stress products and related pathologies are guiding us towards increasingly targeted interventions (preventive, diagnostic, and therapeutic).…”
Section: Discussionmentioning
confidence: 99%